2010
DOI: 10.1002/jsfa.4061
|View full text |Cite
|
Sign up to set email alerts
|

Sensory quality of marama/sorghum composite porridges

Abstract: Combining sorghum meal with full-fat marama bean flour has the potential to improve the sensory quality of sorghum porridge as a staple by providing acceptable sensory appeal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 15 publications
1
16
0
Order By: Relevance
“…The antioxidant activity of sorghum tannins is higher than that of tannins extracted from any other crop. (88,99,110) In animal studies, sorghum tannins have been shown to be [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] fold more effective at quenching peroxyl radicals than simple phenolics. (111) The presence of tannins in sorghum grain may reduce the nutritive value and lower metabolizable energy of the grain.…”
Section: Phenolic Compoundsmentioning
confidence: 99%
See 2 more Smart Citations
“…The antioxidant activity of sorghum tannins is higher than that of tannins extracted from any other crop. (88,99,110) In animal studies, sorghum tannins have been shown to be [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] fold more effective at quenching peroxyl radicals than simple phenolics. (111) The presence of tannins in sorghum grain may reduce the nutritive value and lower metabolizable energy of the grain.…”
Section: Phenolic Compoundsmentioning
confidence: 99%
“…Although numerous studies have been conducted with human subjects (Table 3 (19,29,35,58,67, ), the majority have addressed micronutrient metabolism (such as interactions between leucine, molybdenum, and niacin), (129) iron absorption from cereals, (35) dietary fiber effects, (140) protein digestibility (144) and oral rehydration therapies. (148) This review therefore summarizes the experimental evidence that suggests protective health effects of sorghum consumption, targeting studies that investigate effects on energy balance, glycemic control, lipids, oxidative stress and cell-mediated responses.…”
Section: Experimental Research On Sorghum Consumptionmentioning
confidence: 99%
See 1 more Smart Citation
“…The marama bean flours were prepared as previously described by Maruatona et al (2010) with modifications by Kayitesi et al (2010). Four marama flour samples were prepared and were denoted full fat flour from heated marama beans (FH), full fat flour from unheated marama beans (FUH), partially defatted flour from heated marama beans (DH) and partially defatted flour from unheated marama beans (DUH).…”
Section: Preparation Of Marama Floursmentioning
confidence: 99%
“…Previously, Kayitesi, Duodu, Minnaar and de Kock (2010) found that combining sorghum meal with full fat marama bean flour has the potential to improve the sensory quality of sorghum porridge. These researchers reported in detail on the effects of dry heating or roasting of marama beans, defatting and combining the resultant flours with sorghum meal on the sensory quality of porridges made from the flours in terms of descriptive sensory evaluation, consumer sensory evaluation and objective textural and colour measurements.…”
Section: Introductionmentioning
confidence: 99%